The Rights of Safety and Privacy for the People Infected with Coronavirus from the Social Media Users: The Constitutional and Criminal Protections According to the Jordanian Legislation - Aljazi جهاد ضيف الله; Ehjelah عبدالله محمد (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: This study aims to explain the extent of the constitutional and criminal protection provided by the Jordanian legal system to the rights of tranquility and privacy of people infected with the Coronavirus that might be violated by social media users. Methods: The study followed the analytical approach by analyzing the texts of the defense law and defense orders related to the right of tranquility and privacy for people infected with the Corona virus, to protect them from the violations they are exposed to by social media users. Results: The study reached several results, most notably that Defense Order No. (8) for the year 2002 does not require the existence of a complaint to file a criminal case in the crime of publishing data related to the privacy of Corona patients. Conclusions: The study recommends filing a complaint from the victim as a prior step to start a criminal case on charges of violating the privacy of people infected with the Corona virus.